Knowledge and Attitude of Students in Rafsanjan University of Medical Sciences Regarding Health Measures in Emergency Situations - Seyedeh Shirin Lotfipur Rafsanjani; Mahdiyeh Masoomi; Yaser Salim Abadi; Hadi Eslami; Mostafa Nasirzadeh (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2022)
Background and Objectives: Evaluating knowledge and attitude towards healthy behaviors can help develop educational programs and identify the weakness of people in the field of health information in emergency situations. This study aims to determine the knowledge and attitude of students in Rafsanjan University of Medical Sciences (RUMS) regarding health measures in emergency situations. Methods: This descriptive study was conducted on 425 students of RUMS who were selected using stratified quota sampling method in 2021. The data collection tool was a questionnaire adapted from the study by Vosoughi Nayyeri et al. (2013). After collecting the data, they were analyzed in SPSS software , vertion 18 using independent t-test, one-way ANOVA, and Pearson’s correlation test. The significance level was set at 0.05. Results: The mean scores of knowledge and attitude was 5.2±1.6 (out of 10) and 34.9±2.9 (out of 50), respectively. There was a significant correlation between students’ knowledge and age (r=0.114, P<0.01) and between their attitude and age (r=0.146, P<0.01) such that, with the increase of age, their knowledge and attitude increased. Conclusion: The RUMS students’ knowledge and attitude about health measures in emergency situations are at a moderate level. To improve their knowledge and attitude, educational courses can be held in this regard.